Green synthesis of nitrogen-doped multiporous carbons for oxygen reduction reaction using water-caltrop shells and eggshell waste. Issue 26 (28th April 2021) - Hsu, Chun-Han; Pan, Zheng-Bang; Qu, Hau-Ting; Chen, Chuan-Ren; Lin, Hong-Ping; Sun, I-Wen; Huang, Ching-Ying; Li, Chun-Han
Abstract : A green synthetic method is proposed for the preparation of nitrogen-doped multiporous carbons (denoted as N-MPCs) from water-caltrop-shell (WCS) biochar by using eggshell waste as both a nitrogen-dopant and an activating agent. Abstract : A green synthesis method is proposed for the preparation of nitrogen-doped multiporous carbons (denoted as N-MPCs) from water-caltrop shell (WCS) using eggshell waste as both a nitrogen-dopant and an activating agent. It is shown that the surface area, porosity, yield and nitrogen content of the as-prepared N-MPCs can be easily controlled by adjusting the activation temperature. Moreover, in oxygen reduction reaction (ORR) tests performed in O2 -saturated 0.1 M KOH(aq) electrolyte containing 1.0 M methanol, the N-MPC catalysts show a high ORR stability and good resistance to methanol corrosion. In addition, as a cathode material in Al–air battery tests, the N-MPCs achieve a power density of 16 mW g −1 in a saturated NaCl(aq) electrolyte. Overall, the results show that the N-MPCs have a promising potential as a green and sustainable material for ORR catalysis applications.